Abiotic oxidative transformation of 6-PPD and 6-PPD quinone from tires and occurrence of their products in snow from urban roads and in municipal wastewater - Seiwert, Bettina; Nihemaiti, Maolida; Troussier, Mareva; Weyrauch, Steffen; Reemtsma, Thorsten (Water research (Oxford), 2022)
•38 oxidation products were tentatively identified from tire-derived 6-PPD in the lab.•Most of them were also found in snow from roads, primarily in particle fraction.•Load of 6-PPD and TPs in municipal wastewater peaked during rainfall and snowmelt.•6-PPD and 6-PPDQ of minor importance in WWTP effluent. The antiozonant N-phenyl-N’-(1,3-dimethylbutyl)-p-phenylenediamine (6-PPD) is added to tires to increase their lifetime and is emitted with tire and road wear particles into the environment. Recently, one of its transformation products (TPs), 6-PPD quinone (6-PPDQ), has gained attention due to its toxicity towards coho salmon. In this study, the abiotic oxidative transformation of 6-PPD is investigated by a series of ozonation experiments in the lab followed by analysis of TPs using liquid chromatography-high resolution-mass spectrometry (LC-HRMS). A total of 38 TPs were detected and tentatively identified, which were formed either directly from 6-PPD or via 6-PPDQ as intermediate. A suspect screening by LC-HRMS showed 32 of these TPs to occur in snow collected from urban roads as surrogate of road-runoff, where 6-PPDQ, 4-aminodiphenylamine (4-ADPA), TP 213, and TP 249 were the most prominent besides 6-PPD. More than 90% of the total load of 6-PPD and its TPs was found in the particulate fraction of snow. Thus, retaining the particulate fraction of road runoff before its discharge into surface water would substantially reduce the emission of 6-PPD and many of its TPs. Some TPs prevailed in the water phase of the snow due to their higher polarity. A total of 13 TPs were detected by suspect screening in the dissolved phase of a wastewater treatment plant (WWTP) influent. Their total load was markedly enhanced during a day of snowmelt (approx. 1100 g/d) and rainfall (approx. 2000 g/d) compared to dry weather (approx. 190 g/d). 6-PPD and 6-PPDQ contributed to less than 1% to this total load in the water phase (estimated concentrations of max 0.1 µg/L). The elimination of the estimated total loads of 6-PPD related TPs from the water phase in WWTP ranged from 22 to 67% depending on weather conditions. Eventually TP 249, 4-ADPA and TP 259_2 dominated in WWTP effluent (estimated concentration from 0.5 up to 2 µg/L). Thus TP 249 and TP 259_2 are, likely, the most specific and stable TPs of 6-PPD to be determined in the environment. [Display omitted]